Disclosure of BMTI: one size does not fit all? - Rahmawati, Rahmawati; Ab Rashid, Hafiz-Majdi; Annuar, Hairul Azlan; Siraj, Siti Alawiah (UIN Syarif Hidayatullah Jakarta, 2023)
Micro, small, and medium-sized businesses are defined differently in different parts of the world because of their disparities in economic development. However, the accounting requirements for those three are the same. This study examines the differences in the disclosure of micro, small, and medium Baitul Maal Wat Tamwil Institutions (BMTI). A total of 206 annual reports of BMTIs in Indonesia were divided based on the size of BMTI and then measured in terms of the extent and quality of disclosure by using 60 items under four dimensions of disclosure: general, financial, social, and Shariah compliance. This study used descriptive statistics analysis as well as one-way analysis of variance (ANOVA). The result showed that the micro BMTIs should be grouped into small-scale enterprises while the medium BMTIs are classified into one broad category. Therefore, regulators should establish size-based reporting standards into two classified entities to foster the growth of BMTIs from micro to small, and medium to big sizes.